New Ideas Concerning Science and Technology Vol. 10 - Ferreira, M. A. M. (2021)
This book covers key areas of science and technology research. The contributions by the authors include reading function, computer-based teaching methodology, coincidence detection learning, artificial neural networks’ modeling, artificial neural network modeling, reading brain performance, associative memory, self?organized learning, command and control, bounded rationality constraints, hierarchical, conditional probability density function, computational intelligence and information management, Randic index, sum-connectivity index, transformation graphs, compliment graph, innovative pedagogic approaches, pyrolysis, viscosity, hydrocarbon mixtures, predictive model, finite element method, Timoshenko beam theory, composite materials mechanics, static and dynamic analysis of beams, phase transitions, solar cell materials, structural properties, electronic properties, maximal visible polygon, gradient search, guardhouse problem, diagnosis and management competencies. This book contains various materials suitable for students, researchers and academicians in the field of science and technology.